2000
DOI: 10.1016/s0009-2614(00)00083-x
|View full text |Cite
|
Sign up to set email alerts
|

Test of a simple and flexible S8 model molecule in α-S8 crystals

Abstract: e-mails: clopasto@cnea.gov.ar and gamba@cnea.gov.ar α-S 8 is the most stable crystalline form, at ambient pressure and temperature (STP), of elemental sulfur. In this paper we analyze the zero pressure low temperature part of the phase diagram of this crystal, in order to test a simple and flexible model molecule. The calculations consist in a series of molecular dynamics (MD) simulations, performed in the constant pressureconstant temperature ensemble. Our calculations show that this model, that gives good re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…It also presented a difference of m / z 32 between two consecutive peaks on mass spectral data, suggesting a 32 S nature of the sulfur. The 32 S-NMR spectrum was not performed due to the insufficient quantity of isolated sample but its X-ray (Figure 3) was performed and compound 2 was identified as cyclooctasulfur [27]. Cyclooctasulfur was previously reported from a fungal source [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It also presented a difference of m / z 32 between two consecutive peaks on mass spectral data, suggesting a 32 S nature of the sulfur. The 32 S-NMR spectrum was not performed due to the insufficient quantity of isolated sample but its X-ray (Figure 3) was performed and compound 2 was identified as cyclooctasulfur [27]. Cyclooctasulfur was previously reported from a fungal source [28].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, previous studies showed that many species of Cordia are used as antiviral. To this instance, the leaves water extract of Cordia spinescens was demonstrated to be a potential inhibitor on HIV reverse transcriptase enzyme with IC 50 values of 6–8 μg/mL [27].…”
Section: Resultsmentioning
confidence: 99%
“…Using this simple interaction model we could reproduce, via a series of classical constant temperature-constant pressure simulations, 4,5 the following experimental facts: the crystalline structure, the configurational energy and the lattice, bending and torsional dynamics ͑as given by the calculated density of vibrational modes͒ of ␣-, ␤-, and ␥ -S 8 for T у200 K; the orientational dynamical order-disorder phase transition of ␤ -S 8 and, finally, the solid-liquid phase transition of a cubic disordered sample was calculated near the experimental value. 4, 5 Nevertheless, we found a fact that cannot be reproduced by this simple molecular model: 4,5 when the temperature of an ␣ -S 8 MD sample of 288 molecules is lowered below 200 K, our orthorhombic ␣ -S 8 sample shows a structural phase transition to a monoclinic phase, with a molecular array similar to that of ␣ -S 8 that we called ␣Ј -S 8 . 5 This has not been experimentally observed.…”
Section: Introductionmentioning
confidence: 84%
“…4, 5 Nevertheless, we found a fact that cannot be reproduced by this simple molecular model: 4,5 when the temperature of an ␣ -S 8 MD sample of 288 molecules is lowered below 200 K, our orthorhombic ␣ -S 8 sample shows a structural phase transition to a monoclinic phase, with a molecular array similar to that of ␣ -S 8 that we called ␣Ј -S 8 . 5 This has not been experimentally observed. This spontaneous change was most probably due to the large fluctuations associated with a relatively small sample.…”
Section: Introductionmentioning
confidence: 84%
“…We recently reported [10,11] a series of constant pressure-constant temperature classical MD simulations of α−, β− and γ − S 8 crystals using an extremely simple and flexible molecular model, a slight modification of the one proposed in the constant volume MD simulations of α-S 8 [9]. The simple intermolecular potential was of the Lennard-Jones (LJ) atom-atom type, except that its parameters were fitted in ref.…”
Section: Introductionmentioning
confidence: 99%